Membangun Kesadaran Hukum dan Kemandirian Ekonomi Perempuan Home Industry Kue Melalui Pendampingan Legalitas Usaha di Tulungagung - Dian Ferricha; Amilis Kina (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2026)
Women's increasing participation in the economic sector through home-based industries has become a key pillar of household economic resilience in Kedungsoko Village, Tulungagung Regency. However, most women entrepreneurs still face challenges in obtaining business legality, including a Business Identification Number (NIB), a Home Industry Food Production Certificate (PIRT), and Halal certification due to limited administrative literacy. This community service program aimed to assist women engaged in home-based cake businesses in obtaining business legality to enhance product competitiveness and strengthen household economic independence. The program employed the Asset-Based Community Development (ABCD) approach through stakeholder coordination, technical training on business licensing, and assistance in processing legal documents via the Online Single Submission (OSS) system. The results showed that participants' legal knowledge and awareness increased significantly from 18% to over 90%. A total of 35 participants (70%) obtained a Business Identification Number (NIB), 10 participants (20%) completed the PIRT certification process, and 5 participants (10%) were undergoing Halal certification. The participants' average monthly income increased from IDR 1,200,000 to IDR 1,800,000. In addition, the Kedungsoko Women's Microenterprise Group (KUMPK) was established as a sustainable collaborative platform. The business legality assistance program proved effective in strengthening women's legal and economic empowerment. Keywords: Business Legality Assistance, Women-Owned MSMEs, Home-Based Food Industry Peningkatan keterlibatan perempuan dalam sektor ekonomi melalui industri rumahan menjadi pilar penting bagi ketahanan ekonomi keluarga di Kelurahan Kedungsoko, Kabupaten Tulungagung. Namun, sebagian besar pelaku usaha perempuan masih menghadapi kendala legalitas usaha, seperti Nomor Induk Berusaha (NIB), sertifikat PIRT, dan label halal akibat rendahnya literasi administratif. Kegiatan pengabdian ini bertujuan untuk mendampingi perempuan pelaku home industry kue dalam memperoleh legalitas usaha guna meningkatkan daya saing produk serta kemandirian ekonomi keluarga. Metode yang digunakan adalah Asset-Based Community Development (ABCD) melalui koordinasi pemangku kepentingan, pelatihan teknis perizinan, serta pendampingan pengurusan dokumen melalui sistem OSS. Hasil menunjukkan peningkatan pengetahuan dan kesadaran hukum peserta dari 18% menjadi lebih dari 90%. Sebanyak 35 peserta (70%) memperoleh NIB, 10 peserta (20%) menyelesaikan PIRT, dan 5 peserta (10%) sedang menjalani sertifikasi halal. Pendapatan rata-rata meningkat dari Rp1.200.000 menjadi Rp1.800.000 per bulan. Selain itu, terbentuk Kelompok Usaha Mikro Perempuan Kedungsoko (KUMPK) sebagai wadah kolaborasi yang berkelanjutan. Pendampingan legalitas terbukti memperkuat pemberdayaan hukum dan ekonomi perempuan. Kata kunci: Pendampingan Legalitas Usaha, Perempuan Pelaku UMKM, Industri Rumah Tangga Pangan